2007
DOI: 10.1108/17410390710740763
|View full text |Cite
|
Sign up to set email alerts
|

Enterprise size matters: objectives and constraints of ERP adoption

Abstract: PurposeThe purpose of this paper is to contribute to the discussion on enterprise resource planning (ERP) system adoption by investigating the relationship of enterprise size to the objectives and constraints of ERP adoption.Design/methodology/approachIn the paper, survey data, based on the responses of 44 companies, are analyzed, by dividing the companies into small, medium‐sized, and large enterprises; and comparing these groups, using statistical methods.FindingsThe paper finds significant differences exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
105
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(123 citation statements)
references
References 36 publications
6
105
2
1
Order By: Relevance
“…Previous studies reported that organization dimension strongly influence on the organizational IT adoption of an innovation (Laukkanen et al, 2007). ERP system is an enterprise-wide generic solution, thus during implementation phase it requires vendors to customize the software according to HEIs' requirements.…”
Section: Organizational Dimensionmentioning
confidence: 99%
“…Previous studies reported that organization dimension strongly influence on the organizational IT adoption of an innovation (Laukkanen et al, 2007). ERP system is an enterprise-wide generic solution, thus during implementation phase it requires vendors to customize the software according to HEIs' requirements.…”
Section: Organizational Dimensionmentioning
confidence: 99%
“…SMEs also lack the latest technology, IT infrastructure and the quantity and quality of available business data [30]. These limitations become an obstacle in ERP implementation or in adjusting to ERP after its deployment [31]. …”
Section: Constraints Of Standard Erp Adoption In Smesmentioning
confidence: 99%
“…Hence, companies are differentiated into small and medium-sized enterprises on the one hand and large companies such as multi-national enterprises on the other hand. The former shall comprise organizations with up to 250 employees [28].…”
Section: Context Factorsmentioning
confidence: 99%